Pengetahuan Remaja Putri Terhadap Dampak Pernikahan Dini - Nora Rahmanindar Nora; Iroma Maulida; Vika Nurhaliza (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2020)
According to the Indonesia Population Data Survey (IDHS), the number of cases of early marriage in Indonesia reaches 50 million people with an average marriage age of 19.1 years. Teen pregnancy will increase the risk of death 2-4 kli higher than pregnancy at the age of> 20 years because it will endanger the health of mother and baby, such as maternal and infant mortality, risk of pregnancy complications, delivery complications, post partum hemorrhage, risk of abortion, severe low birth weight (LBW) and cervical cancer are cases experienced by women who marry early. This study aims to determine the Description of Adolescent Knowledge Against the Impact of Early Marriage in Bojong Village, Bojong Subdistrict, Tegal Regency in 2019. The design and type of this research was descriptive research through a cross sectional approach with a purposive sampling technique. The population was young women aged 15-17 years as many as 350 people and found 78 respondents. The results of this study can be obtained by young women interviewed by researchers mostly aged 16 years as many as 47.4%, educated junior high school (SMP) as much as 55.1% and not working as much as 75.6%. The description of adolescent girls' knowledge of the effects of early marriage was mostly included in the good category at 91%. Keywords : Young Women, Early Marriage. ABSTRAK Menurut Survei Data Kependudukan Indonesia (SDKI), jumlah kasus pernikahan dini di Indonesia mencapai 50 juta penduduk dengan rata-rata usia perkawinan 19,1 tahun. Kehamilan remaja akan meningkatkan risiko kematian 2-4 kli lebih tinggi dibandingkan hamil pada usia > 20 tahun karena akan membahayakan kesehatan ibu dan bayinya, seperti kematian ibu dan bayi, risiko komplikasi kehamilan, komplikasi persalinan, terjadinya perdarahan post partum, risiko terjadinya abortus, berat badan lahir rendah (BBLR) dan kanker serviks adalah kasus yang dialami oleh wanita yang menikah dini. Penelitian ini bertujuan untuk mengetahui Gambaran Pengetahuan Remaja Terhadap Dampak Pernikahan dini di Desa Bojong Kecamatan Bojong Kabupaten Tegal Tahun 2019. Rancangan dan jenis penelitian ini adalah penelitian deskriptif melalui pendekatan cross sectional dengan teknik pengambilan sampel purposive sampling. Populasinya remaja putri usia 15-17 tahun sebanyak 350 orang dan didapatkan78 responden. Hasil penelitian ini di dapat adalah remaja putri yang diwawancarai oleh peneliti sebagian besar berumur 16 tahun sebanyak 47.4%, berpendidikan Sekolah Menengah Pertama (SMP) sebanyak 55.1% dan tidak bekerja sebanyak 75.6%. Gambaran pengetahuan remaja putri terhadap dampak pernikahan dini sebagian besar termasuk dalam kategori baik yaitu sebanyak 91%. Kata Kunci : Remaja Putri, Pernikahan Dini.